Literature review pengaruh pemberian bekam basah terhadap hipertensi - Annisa Aina Fitria; Tri Hardi Miftahul Ulum; Ignasia Nila Siwi (MEDIA ILMU KESEHATAN, 2022)
Background: Hypertension is a non-communicable disease that is one of the causes of mortality in the world. Hypertension is often referred to as the silent killer because it is often without complaints, a serious condition that significantly increases the risk of heart, brain, kidney, and other diseases. Complications in patients with hypertension can be life-threatening, so pharmacological therapies is wet cupping which can lower blood pressure. Objective: The purpose of this study was to determine the effect of wet cupping on hypertension. Methods: The method in this study uses the PICOS framework, namely Population/problem (P), Intervention (I), Comparison (C), Outcome (O), and study design (S). In the early stages of article selection, 68 articles were found from the PubMed database, ProQuest, Elsevier, Science Direct, Google Scholar, Harvard Library, Springer Link, ResearchGate, Taylor and Francis search engine after further matching, 60 article were selected, then 53 articles were excluded because they were not appropritate. With problems, intervention, study design, and no effect of wet cupping on hypertension so that 7 articles were obtained that matched the research topic. Results: The results of the search that wet cupping affects hypertension, this is evidenced from before and after the wet cupping intervention was given, namely there was a significant decrease in systole and diastole with p-value <0,05. This wet cupping treatment is more effective, given once a month for satisfactory results with an adminstration time of 15-30 minutes.Conclusion: This treatment is highly recommended to the general public, health clinics, hospitals, and health workers and this treatment provides many benefits.